Cav1 inhibits benign skin tumor development in a two-stage carcinogenesis model by suppressing epidermal proliferation - Trimmer, Casey; Sotgia, Federica; Lisanti, Michael P; Capozza, Franco (American journal of translational research, 2013)
Caveolin-1 (Cav1) is the main protein component of the membrane lipid rafts caveolae. Cav1 serves as a scaffolding protein that compartmentalizes a multitude of signaling molecules and sequesters them in their inactive state. Due to its function in the negative regulation of signal transduction, loss of Cav1 has been implicated in the pathogenesis of many cancers, but its role in cutaneous squamous cell carcinoma (cSCC) is largely unexplored. cSCC is a multi-stage disease characterized by the development of benign, premalignant lesions and their progression into malignant cancer. Here, we use a two-stage carcinogenesis protocol to elucidate the function of Cav1 in the different stages of benign papilloma development: initiation and promotion. First, we demonstrate that Cav1 knock-out (KO) mice are more susceptible to benign papilloma development after being subjected to a DMBA/TPA initiation/promotion protocol. Treatment of wild-type (WT) and Cav1 KO mice with DMBA alone shows that both groups have similar rates of apoptosis. In contrast, treatment of these groups with TPA alone indicates that Cav1 KO mice are more susceptible to promoter treatment as evidenced by increased epidermal proliferation. Furthermore, primary keratinocytes isolated from Cav1 KO mice have a proliferative advantage over WT keratinocytes in both low- and high-calcium medium, conditions that promote proliferation and induce differentiation, respectively. Collectively, these data indicate that Cav1 functions to suppress proliferation in the epidermis, and loss of this function promotes the development of benign skin tumors.